2013
DOI: 10.1007/s12253-013-9735-9
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological Features and Prognosis of Pregnancy Associated Breast Cancer – A Matched Case Control Study

Abstract: Pregnancy Associated Breast Cancer (PABC) manifests during pregnancy or within a year following delivery. We sought to investigate differences in management, outcome, clinical, histopathology and immunohistochemistry (IHC) characteristics of PABC and matched controls in a retrospective case control study. PABC and control patients were selected from breast cancer cases of women ≤45 years, diagnosed in the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
59
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(67 citation statements)
references
References 37 publications
4
59
0
4
Order By: Relevance
“…Luminal B breast cancer accounted for the largest proportion of all PABC patients, followed by triple-negative breast cancer. Consistent with our study, Soo reported that luminal B breast cancer (43.6%) and TNBC (35.9%) predominated in PABC [8]; while one study presented a different conclusion and showed that TNBC ranked first (48.4%) [9]. Some studies did not list the molecular types but reported the HR and HER-2 status and demonstrated that PABC was more prone to be HR-negative tumors, but no difference in the HER-2 status was reported compared with non-PABC as follows: HR negative (50.0% in PABC vs. 36.1% in non-PABC, P<0.001 (Yun et al)) [10], HR negative (32.6% in PABC vs. 15.9% in non-PABC, P=0.014 (Jessica et al)) [11], and HR negative (59.4% in PABC vs. 34.4% in non-PABC, P=0.03 (Michael et al)) [12]; only one study reported by Soo showed a higher HER-2 positive rate in PABC patients as follows: HER-2 positive (38.5% in PABC vs.…”
Section: Discussionsupporting
confidence: 89%
“…Luminal B breast cancer accounted for the largest proportion of all PABC patients, followed by triple-negative breast cancer. Consistent with our study, Soo reported that luminal B breast cancer (43.6%) and TNBC (35.9%) predominated in PABC [8]; while one study presented a different conclusion and showed that TNBC ranked first (48.4%) [9]. Some studies did not list the molecular types but reported the HR and HER-2 status and demonstrated that PABC was more prone to be HR-negative tumors, but no difference in the HER-2 status was reported compared with non-PABC as follows: HR negative (50.0% in PABC vs. 36.1% in non-PABC, P<0.001 (Yun et al)) [10], HR negative (32.6% in PABC vs. 15.9% in non-PABC, P=0.014 (Jessica et al)) [11], and HR negative (59.4% in PABC vs. 34.4% in non-PABC, P=0.03 (Michael et al)) [12]; only one study reported by Soo showed a higher HER-2 positive rate in PABC patients as follows: HER-2 positive (38.5% in PABC vs.…”
Section: Discussionsupporting
confidence: 89%
“…The increased concentration of gestational hormones with growth promoting effects (i.e., estrogen, insulin-like growth factor 1, and progesterone) might result in a more aggressive breast cancer biology [9]. Although some studies did not reveal any major different expression of breast cancer biomarkers (e.g., hormone receptors and HER2) compared with non-pregnant age-matched breast cancer patients [10][11][12], other studies showed that BCP is more commonly associated with unfavorable tumor biology reflected by the predominance of triple-negative breast cancers [13][14][15]. Recently, a series of experiments showed that BCP is associated with specific activated signaling pathways, high expression of potentially relevant cancer targets like SRC, Wnt/b-catenin, RANKL [16,17], and, in addition, low expression of tumor infiltrating lymphocytes [18].…”
Section: Introductionmentioning
confidence: 99%
“…The survival rates of the PABC patients compared to those of the non-PABC patients were conflicting. Most studies [8,9,15,10,14,[16][17][18][19][20][21][22]] demonstrated a worse prognosis in PABC after excluding prognostic factors, including age, the tumor size, and lymph node status, while eight studies [23][24][25][26][27][28][29][30] showed no difference in survival between PABC and non-PABC patients after correcting for these factors.…”
Section: Discussionmentioning
confidence: 99%